Haemoglobin And Porphyrin Encapsulated Self-Assembled Polymers As Artificial Oxygen Carrier - Othman, Mislia (2023)
Blood transfusion services have a lot of risks such as blood-associated risk, blood incompatibility and shortage of blood supply. To address this issue, researchers explored an artificial oxygen carrier through macromolecules by mimicking the structure of human haemoglobin. The aim of this study is to develop haemoglobin and porphyrin encapsulated self-assembled polymers as artificial oxygen carrier. A porphyrin derivative, tetrakis-4-phenyl porphyrin (TPP) was first synthesised through the reaction of pyrrole and 4-benzaldehyde following the addition of iron, Fe(III) forming tetrakis-4-phenyl porphyrin Fe(III) (TPP Fe(III)). Methoxy-polyethylene glycol (mPEG45) block and poly (ɛ-caprolactone) (ɛ-CL) (mPEG-b-PCL) that formed diblock copolymer and para-nitrophenol core and glycidol that formed hyperbranched polyglycidol (HPG) was synthesised via ring-opening polymerisation (ROP). Extra cted Hb and synthesised TPP Fe(III) were then encapsulated in micelle system with a critical micelle concentration (CMC) at 1.0-2.0 mg/ml and hyperbranched polyglycidol prepared in equal molar to Hb and TPP Fe(III) concentration. The average encapsulation efficiency (EE%) of human Hb-micelle and TPP Fe(III)-micelle were 67 ± 5.39% and 78 ± 1.38% as compared to 68 ± 2.22% of bovine Hb-micelle. On the other hand, the EE% of human Hb-HPG and TPP Fe(III)-HPG were 58 ± 6.87% and 22 ± 7.12% as compared to 65 ± 9.11% of bovine Hb-HPG.